The vision of Arabian journalism and Algiers agreement between Iraq and Iran 1975 AL-Rai and AL-Dustur and the Lebanese ALnahar, as a samples - Al - Jawadi, Ghassan W. (Humanities Journal of University of Zakho, 2016)
The vision of Arabian journalism and Algiers agreement between Iraq and Iran 1975 A sample of AD dusotur and Al rai-Daily ordination An-nahar Lebanese Newspapers are considered as a primary source for writing history. In some countries, they reflect the political agenda of their governments when reporting news and incidents occurring in other countries. However, there are some other newspapers that take a completely neutral position and are not influenced by the authority. As rich historical document two newspapers have been chosen, the Jordanian s AL-Rai and AL-dustur and the Lebanese AL-nahar, as samples to view their position on and how they reported the Algiers Accords in 1975 between Iraq and Iran which ended the Kurdish revolution against the Iraqi regime after many years of war. Through studying these newspaper ,the level of interest in this historical moment , and to the Kurdish cause generally , can be shown and the position of their governments in these events whether positive or negative .The latest news and developments about this agreement were mostly published in the first pages which demonstrate that a great deal of attention was given to this agreement ,Thus contributing in documenting the events as they witnessed it and wrote about it .